Class 3 Obesity in a Multidisciplinary Metabolic Weight Management Program: The Effect of Preexisting Type 2 Diabetes on 6-Month Weight Loss - David M. Medveczky; Raymond Kodsi; Kathryn Skelsey; Kathy Grudzinskas; Flavia Bueno; Vincent Ho; Nic Kormas; Milan K. Piya (Journal of Diabetes Research)
Introduction. Class 3 obesity (BMI≥40 kg/m2) is a growing health problem worldwide associated with considerable comorbidity including Type 2 diabetes mellitus (T2DM). The multidisciplinary medical management of obesity can be difficult in T2DM due to potential weight gain from medications including sulphonylureas and insulin. However, newer weight-neutral/losing diabetes medications can aid additional weight loss. The aim of this study was to compare weight loss outcomes of patients with and without T2DM, and in patients with T2DM, to compare diabetes outcomes and change in medications at 6 months. Methods. All patients entering a multidisciplinary weight management metabolic program in a publicly funded hospital clinic in Sydney between March 2018 and March 2019, with BMI≥40 kg/m2 and aged ≥18 years were included. Data was collected from patient clinical and electronic notes at baseline and 6 months. Results. Of the 180 patients who entered the program, 53.3% had T2DM at baseline. There was no difference in percentage weight loss in those with or without T2DM (4.2±4.9% vs. 3.6±4.7%, p=0.35). Additionally, T2DM patients benefited from a 0.47% reduction in HbA1c (p<0.01) and a reduction in the number of medications from baseline to 6 months (1.8±1.0/patient vs. 1.0±1.2/patient, p<0.001). T2DM patients who started on weigh-neutral/losing medications in the program lost more weight than those started on weight-gaining medications (7.7±5.3% vs. 2.4±3.8%, p=0.015). Conclusions. Patients with class 3 obesity had significant weight loss at 6 months in this program. Patients with T2DM at baseline had comparable weight loss at 6 months, a significant improvement in glycaemic control, and a reduction in diabetes medication load. Additionally, patients with T2DM who were started on weight-neutral/losing medications lost significantly more weight than those started on weight-gaining medications, and these medications should be preferentially used in class 3 obesity and comorbid T2DM.